Scala Archives : Immagini digitali professionali d'arte e cultura - Scala Archives (2007)
[Dt.:] Scala Archives, gegründet 1953 auf Initiative des italienischen Kunsthistorikers Roberto Longhi, ist als offizielle Photoagentur für zahlreiche italienische Museen sowie Museen außerhalb Italiens tätig und verfügt über eine der umfangreichsten zur Zeit verfügbaren Sammlungen an digitalisiertem Photomaterial aus den Bereichen Kunst, Kultur, Reise. Die Herausgabe von Bildmaterial an Dritte zum Zwecke der Publikation erfolgt gegen Gebühr. Die Seite bietet Informationen über das Archiv, kooperierende Museen und Institutionen, allgemeine Informationen zur Suche, Bestellung und Nutzung von Bildmaterial sowie zum Copyright. Eine Suchfunktion ermöglicht die Recherche in Echtzeit. - [Engl.:] THE SCALA ARCHIVES can be considered the "official" photographic agency of innumerable museums in Italy and abroad, as well as the largest and most prestigious catalogue of images from the worlds of art, culture and travel available in digital form today. The images are hired out for reproduction to publishers, TV networks, periodicals, companies, institutions, graphic art studios and advertising, photographic and travel agencies throughout the world, with the aim of diffusing, with a strong cultural bias, the knowledge and study of works of art. Customers can obtain access to the images by logging onto the site www.scalarchives.it, and above all through the free thematic search service provided by the Library's expert picture researchers (archivio scalagroup.com), who on request will supply color transparencies or image files by e-mail. A sophisticated program for internal use makes it possible to find images relating to over 7000 keywords. Users can carry out searches in real time and place orders for pictures by e-mail from within the catalogue itself. The catalogue is updated monthly to include new photographic campaigns and selective acquisitions.